2013
DOI: 10.1016/j.placenta.2013.06.308
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products enhances soluble Fms-like tyrosine kinase 1 expression in trophoblasts: A possible link between oxidative stress and preeclampsia

Abstract: Accumulation of advanced oxidation protein products (AOPPs) is prevalent in obesity, advanced maternal age, diabetes mellitus, and polycystic ovary syndrome. Alterations in the regulation and signaling of angiogenic pathways have been recognized as a link between these conditions and pre-eclampsia. To investigate the possible impact of AOPPs on soluble Fms-like tyrosine kinase 1 (sFlt-1) expression in trophoblasts. A trophoblast cell line (HRT-8/SVneo) was treated with various concentrations of AOPPs. The mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 32 publications
(34 reference statements)
0
23
1
2
Order By: Relevance
“…This finding is in contrast to an earlier study which showed that the levels of AOPP did not change significantly among the control, pre-eclampsia and eclampsia groups [26]. AOPP's are important mediators in the regulation and signaling of angiogenic pathways of trophoblasts, enhancing soluble Fms-like tyrosine kinase 1 expression in trophoblasts, promoting the development of preeclampsia [27]. Whether AOPP mediates similar signaling pathways as an attributable mechanism for development of other different hypertensive disorders is yet to be explored.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in contrast to an earlier study which showed that the levels of AOPP did not change significantly among the control, pre-eclampsia and eclampsia groups [26]. AOPP's are important mediators in the regulation and signaling of angiogenic pathways of trophoblasts, enhancing soluble Fms-like tyrosine kinase 1 expression in trophoblasts, promoting the development of preeclampsia [27]. Whether AOPP mediates similar signaling pathways as an attributable mechanism for development of other different hypertensive disorders is yet to be explored.…”
Section: Discussioncontrasting
confidence: 99%
“…These effects are able to be inhibited by a combination of apocynin and NOX inhibitors. Therefore, accumulation of AOPPs might contribute to the pathogenesis of preeclampsia by promoting sFlt-1 production in trophoblasts [ 72 ].…”
Section: Cellular Sources Of Oxidative Stress In the Human Placentmentioning
confidence: 99%
“…Implicit in this generalized endothelial dysfunction may be an imbalance of angiogenic and anti-angiogenic factors ( 26 28 ). Both circulating and placental levels of soluble fms-like tyrosine kinase-1 (sFlt-1) are higher in women with preeclampsia than in women with normal pregnancy ( 29 31 ). sFlt-1 is an anti-angiogenic protein that antagonizes vascular endothelial growth factor (VEGF) and PIGF ( 32 34 ), both of which are pro-angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%